2020
DOI: 10.1177/0093854820942285
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Housing Circumstances on Recidivism: Evidence From a Sample of People on Probation in San Francisco

Abstract: The relationships between housing circumstances and recidivism are well established among people released from prison. Despite probation being far more common than prison or parole, we know little about living situations, homelessness, and residential instability among people on probation, and we know even less regarding how these housing circumstances may affect their risk of recidivism. Using a unique dataset of 2,453 people on probation and longitudinal analyses, this study finds that housing insecurity is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 50 publications
3
28
0
Order By: Relevance
“…We excluded people ( n = 3566) who had no mappable address in San Francisco (59%; i.e., relocated/transferred outside the city, documented as homeless, or lacked a residential address) or who were not assessed for risk with the COMPAS at the start of probation (46%). Our inclusion rate (38%) is low but comparable to similar studies (e.g., Wolff et al, 2018), especially given this region’s high rate of homelessness (see Jacobs & Gottlieb, 2020). To assess potential selection bias, we compared the characteristics of our final sample with those excluded.…”
Section: Methodssupporting
confidence: 88%
See 1 more Smart Citation
“…We excluded people ( n = 3566) who had no mappable address in San Francisco (59%; i.e., relocated/transferred outside the city, documented as homeless, or lacked a residential address) or who were not assessed for risk with the COMPAS at the start of probation (46%). Our inclusion rate (38%) is low but comparable to similar studies (e.g., Wolff et al, 2018), especially given this region’s high rate of homelessness (see Jacobs & Gottlieb, 2020). To assess potential selection bias, we compared the characteristics of our final sample with those excluded.…”
Section: Methodssupporting
confidence: 88%
“…Second, we used participants’ addresses at the start of probation to characterize their neighborhood, even though some participants moved after probation began. We used participants’ addresses at the start of probation because this is when addresses were most reliably documented and because most participants did not have a residential move during the observation period (see Jacobs & Gottlieb, 2020). Third, our use of data related to residential contexts immediately proximate to participants did not fully address error that can arise based on how geographic units are defined (the modifiable areal unit problem; MAUP) and may not reflect contextual influences that participants predominately experience, if they spend much time elsewhere (i.e., the uncertain geographic context problem; UGCP).…”
Section: Discussionmentioning
confidence: 99%
“…One retrospective study found that incarcerated populations experienced significant residential instability prior to detention, which illustrates the pathway from housing instability into first incarceration (Muentner et al 2019). Yet the strongest evidence comes from studies of recidivism showing that unstable housing after incarceration increases the likelihood of reoffending and thus reincarceration (Clark 2016;Jacobs and Gottlieb 2020;Steiner, Makarios, and Travis 2015). The reverse is also true: programs that provide stable housing for formerly incarcerated people facilitate reintegration and reduce recidivism (Cobbina 2010;Kirk et al 2018).…”
Section: Monetary Sanctions and Housing Instabilitymentioning
confidence: 99%
“…Many housing and accommodation applications in the USA require reference checks, credit checks, and previous employment checks (Leasure, 2019;Simes, 2019;Jacobs and Gottlieb, 2020). My previous crimes led me (Adam) to serve a lengthy period of incarceration and I had only been released two months prior.…”
Section: Housingmentioning
confidence: 99%
“…This type of discrimination is common to previously incarcerated people and in this, instance their partner (Evans et al, 2019). The requirements around gaining housing or accommodation are not designed with previously incarcerated people in mind and the checks and balances required make it near impossible for many (Hatami, 2019;Leasure, 2019;Jacobs and Gottlieb, 2020).…”
Section: Housingmentioning
confidence: 99%